Physical and Sexual Intimate Partner Aggression Among College Students: Examining the Roles of Cyber Intimate Partner Aggression and Alcohol Use - Watkins, Laura E. (Journal of interpersonal violence, 2022)
Intimate partner aggression (IPA) is a serious and prevalent problem among college students. Two factors that may increase risk for in-person IPA are cyber IPA and alcohol use. This study examines the interaction between three types of cyber IPA (cyber psychological, stalking, and sexual IPA) and alcohol use in predicting in-person physical and sexual IPA perpetration. Participants were 268 undergraduate students, who participated in a mass screening at a large midwestern university. More than half of the sample reported perpetrating cyber IPA. A multivariate logistic regression model was used to examine study hypotheses. The R2 for physical IPA perpetration was .69 and the R2 for sexual IPA perpetration was .46. Cyber stalking IPA and alcohol interacted to predict physical IPA perpetration, such that the relationship between cyber stalking IPA and physical IPA perpetration was stronger among individuals who used more alcohol. Contrary to expectations, cyber IPA and alcohol did not interact to predict sexual IPA. However, consistent with hypotheses, cyber stalking IPA was positively associated with sexual IPA perpetration. The high prevalence of cyber IPA and its association with in-person IPA perpetration suggests that prevention programs targeting cyber IPA on college campuses may be warranted.